An Approach to Robustness Evaluation for Sequential Testing under Functional Distortions in L1-metric - Alexey Kharin; Sergey Chernov (Austrian Journal of Statistics, 2014)
The problem of sensitivity analysis for the sequential probability ratio test under func- tional distortions of the observation probability distribution is considered. For the situa- tion where distorted densities of the log likelihood ratio statistic belong to ?-neighborhoods of hypothetical centers in the L1-metric the least favorable distributions that maximize the conditional error probabilities are constructed. The instability coefficient is obtained to enable robustness evaluation for the sequential probability ratio test and its modification – trimmed sequential probability ratio test.